Ammonia Gas Leak Alert System for Laboratory Using MQ-135 Gas Sensor and GSM Application - Ramle, Rashidah; Ahmad Fairuz, Muhammad Daniel Arif; Ramle, Rosni; Yusuf, Muhammad Fakhrul (Penerbit UTHM, 2020)
Mobile Alert System for Ammonia Gas Leak using Arduino and GSM application is a system that helps to detect the presence of ammonia gas in the laboratory thus alerting the person in charge such as laboratory technician. The system is based on Arduino UNO, GSM SIM900 module, and MQ-135 gas sensor. The prototype consists of a single sensor, which is MQ-135 gas sensor that is mainly responsible for detecting ammonia gas. The function of this prototype is whenever the ammonia gas is detected within the gas sensor’s range inside the laboratory, it will trigger an alarm sound thus giving an alert message to the laboratory technician. Besides, this project has also identified the best placement to implement the sensor in the laboratory. It is based on the analysis of different distances between the gas sensor and the gas released. This system is very beneficial to the people who are using the laboratory because it can give immediate alert to them for fast action in case when there is a chemical accident occurs that releases harmful gas without anyone noticing it. Furthermore, when there is an increase of distance between the gas sensor and the gas released, the response time required to trigger the alert would also increase. Hence, the optimal implementation to place the gas sensor would be at a range of 80 cm from the gas sensor to the gas chamber, as it requires the shortest time to trigger the alert with a reasonable distance.